Recurrent retroperitoneal liposarcoma with multiple surgeries: a case report - Wang, Xiao; Song, Xiaobiao; Song, Qiang; Wang, Jijun; Chen, Junsheng (Frontiers in Oncology, 2024)
Retroperitoneal liposarcoma (RPLPS) is a rare malignant tumor that is typically treated with surgical resection. However, RPLPS often has a high rate of local recurrence, making it crucial to explore new treatment options. In this report, we present the case of a middle-aged woman who experienced seven recurrences and underwent seven surgeries following the initial resection. Currently, the patient’s condition remains stable after the eighth surgery. Although there have been numerous reports of RPLPS cases both domestically and internationally, instances of repeated recurrence like this are exceptionally rare. Therefore, we have gathered the patient’s case data and conducted a retrospective analysis, incorporating relevant literature, to enhance the understanding of this disease among clinical practitioners.